Trying to solve xy'= xy + y using the series y(x) = $\sum\limits_{i=0}^\infty a_nx^n$ This is what i have so far.

y'(x)= $\sum\limits_{i=0}^\infty na_nx^{n-1}$

xy' - xy - y = 0

x $\sum\limits_{i=0}^\infty na_nx^{n-1}$ - x $\sum\limits_{i=0}^\infty a_nx^n$ - $\sum\limits_{i=0}^\infty a_nx^n$ = 0

$\sum\limits_{i=0}^\infty na_nx^{n}$ - $\sum\limits_{i=0}^\infty a_nx^{n+1}$ - $\sum\limits_{i=0}^\infty a_nx^n$ = 0

then i re-index the second term to get an $x^n$ term

$\sum\limits_{i=0}^\infty na_nx^{n}$ - $\sum\limits_{i=1}^\infty a_{n-1}x^{n}$ - $\sum\limits_{i=0}^\infty a_nx^n$ = 0

Now i'm trying to get a recursion relation but seem to be a little stuck here, I get from n=0 that

$a_0$ = 0

then for n = 1

$na_1$ - $a_0$ - $a_1$ = 0

I think I'm close, just a little confuse with the indexing and how to actually create the recursion relation to solve this. Any help would be greatly appreciated. Thanks!


I would say:

It is necessary to use the series $y=\sum\limits_{i=0}^\infty a_nx^{n+r},\,\,y'=\sum\limits_{i=0}^\infty (n+r)a_nx^{n+r-1}$ and determine the appropriate number r:

xy' - xy - y = 0

$\sum\limits_{i=0}^\infty (n+r)a_nx^{n+r}-\sum\limits_{i=0}^\infty a_nx^{n+r+1}-\sum\limits_{i=0}^\infty a_nx^{n+r}=0$


$(0+r)a_0-a_0=0 \Rightarrow a_0(r-1)=0 \Rightarrow r = 1$

$(n+r)a_n-a_{n-1}-a_n = 0 \Rightarrow a_n=\frac{a_{n-1}}{(n+r-1)_{r=1}}\Rightarrow a_n=\frac{a_{n-1}}{n},\,\,\, n \ge 1$


$a_n=\frac{a_0}{n!}\Rightarrow y=\sum\limits_{i=0}^\infty \frac{a_0}{n!}x^{n+1}=a_0xe^x$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.